LA VOCACIÓN, CLAVE DE RESILIENCIA EN LA PROFESIÓN DOCENTE - Sabino, Carmen Dionicia (HOLOS, 2023)
The vocation, key to resilience in the teaching profession, intends to incorporate new reflections on these constructs from a pedagogical, human, and transcendent perspective; entry into Venezuelan teachers who assume professional commitment in the context marked by an anthropological and educational crisis accentuated by the pandemic. It is the product of research on the vocation to enhance resilience in Venezuelan primary school teachers. Both constructs: vocation and resilience, are imposed as necessary here and now. Discussing about it allows us to extract keys of sense and meaning in exceptional contexts. Following a mixed methodology and rigorously mixed method, information was obtained through interviews and a psychometric instrument. Content analysis and descriptive statistics were applied. The results indicated keys for the understanding of the vocation as a property of the profession and drive force of the resilient mood virtually present in the human being that gives meaning in critical scenarios.